Speech Therapy for Post Thyroidectomy Patients: A Clinical Audit - Amir Hamza Khan, Kashif Ullah Khan, Iqbal Zaman, Ihtisham Ul Haq, Syed Majid Ali Shah, Jawad Mabood (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: We aim to audit the provision of speech counselling to those patients who underwent thyroidectomy for their respective diseases who presented to surgery department in 2021 Methodology: This clinical audit was conducted in surgical D unit department of Surgery, Khyber Teaching Hospital, Peshawar from January 2021 to November 2022. A total of 50 patients each for the audit group and the re-audit group were selected through non-probability consecutive sampling for both genders. A predesigned proforma According to clinical practice guidelines and British association of endocrine and thyroid surgeon’s guidelines (BAETS) was used. Data was entered into Microsoft excel, analyzed through SPSS version 23 and results were presented in the form of descriptive writing and tables. Results: The mean age of the study population was 42.64 +/- 11.51 with relatively more female patients. None of the patients in the audit group were properly given speech counselling irrespective of their disease or surgery status. In the re-audit group, 100% of the patients were given proper post-operative speech therapy which resulted in 84% percent of the patients attaining their usual voice, seven patients having some roughness in their tone and only one patient having occasional problems with breathing. Conclusion: Despite their rarity, voice changes after a straightforward thyroidectomy can be quantified. For ethical and legal reasons, this is significant in the preoperative and postoperative counselling of patients before thyroidectomy.